Endovascular Repair of Thoracic Aorta Injury: 17 Years of Single-Center Experience - Procházka, Václav; Roman, Jan; Jalůvka, František; Jonszta, Tomáš; Vrtková, Adéla; Pleva, Leopold; Ječmínek, Vladimír; Sieja, Jiří; Brát, Radim (Medical science monitor, 2021)
BACKGROUND Traumatic thoracic aortic transection is one of the most severe complications of high-energy injuries, but patients rarely receive treatment, and it is fatal in the vast majority of cases. Due to the complexity of surgical revision for transection, endovascular repair with stent graft implantation is the preferred approach. MATERIAL AND METHODS We retrospectively analyzed the short-term and long-term treatment results for 31 patients (29 men, 2 women) treated at the Interventional Radiology Department, University Hospital Ostrava, for the isthmus part of a descending thoracic aorta injury between 2004 and 2020. RESULTS The median patient age was 48 years (interquartile range [IQR]: 28-63 years). The most common causes of injury were traffic accidents and falls or jumps, with the trauma location at the Ishimaru zones 2 to 4 of the aortic isthmus. Aortic stent grafts were successfully implanted in all patients; 13% of patients had complications and 10% died due to the trauma severity. The median procedure duration was 30 min (IQR: 25-43 min) and the median hospital stay was 29 days (IQR: 28-63 days). CONCLUSIONS Aortic stent graft implantation appears to be a safe and effective method for dealing with thoracic aorta injury, with a low complication rate and high patient survival. The endovascular approach is the method of choice for treating this severe disease, and a multidisciplinary approach for emergency medical treatment with a comprehensive trauma protocol is essential.
Keywords: Retrospective Studies; Česká republika; výsledek terapie; Middle Aged; mužské pohlaví; aorta thoracica; Adult; Czech Republic; ženské pohlaví; retrospektivní studie; Humans; poranění hrudníku; endovaskulární výkony; lidé středního věku; Endovascular Procedures; Thoracic Injuries; dospělí; Female; Treatment Outcome; Aorta, Thoracic; lidé; Male